Angiographic Analysis of the Anatomical Variants in Genicular Artery Embolization - Bagla, Sandeep; Piechowiak, Rachel; Sajan, Abin; Orlando, Julie; Canario, Diego A. Hipolito; Isaacson, Ari (Journal of Clinical Interventional Radiology ISVIR, 2021)
Purpose Genicular artery embolization (GAE) has been proposed as a novel technique to treat painful synovitis related to osteoarthritis. An in-depth understanding of the genicular arterial anatomy is crucial to achieve technical success and avoid nontarget-related complications. Given the lack of previous angiographic description, the present study analyzes genicular arterial anatomy and proposes an angiographic classification system.Materials and Methods Angiographic findings from 41 GAEs performed during two US clinical trials from January 2017 to July 2019 were reviewed to analyze the anatomical details of the following vessels: descending genicular artery (DGA), medial superior genicular artery (MSGA), medial inferior genicular artery (MIGA), lateral superior genicular artery (LSGA), lateral inferior genicular artery (LIGA), and anterior tibial recurrent artery (ATRA). The diameter, angle of origin, and anastomotic pathways were recorded for each vessel. The branching patterns were classified as: medially, M1 (3/3 arteries present) vs M2 (2/3 arteries present); and laterally, L1 (3/3 arteries present) vs L2 (2/3 arteries present).Results A total of 91 genicular arteries were embolized: DGA (26.4%), MIGA (23.1%), MSGA (22.0%), LIGA (14.3%), and LSGA/ATRA (14.3%). The branching patterns were: medially = M1, 74.4% (n = 29), M2, 25.6% (n = 10); and laterally = L1, 94.9% (n = 37), L2, 5.1% (n = 2). A common origin for MSGA and LSGA was noted in 11 patients (28.2%). A direct DGA origin from the popliteal artery was reported in three patients (7.7%, n = 3).Conclusions A thorough understanding of the geniculate arterial anatomy is important for maximizing postprocedural pain reduction while minimizing complications, procedure time, and radiation exposure during GAE.
Keywords: genicular artery embolization; osteoarthritis; angiographic anatomy